Wrist Posture Estimation Differences and Reliability Between Video Analysis and Electrogoniometer Methods. (November 2021) - McKinnon, Colin D.; Ehmke, Samantha; Kociolek, Aaron M.; Callaghan, Jack P.; Keir, Peter J.
Objective: The aim of this study was to determine the inter- and intrarater agreement of estimated wrist angles using video and to compare wrist angles from video analysis to electrogoniometers. Background: Video analysis is used frequently in ergonomic assessments, but factors including parallax and complex angles may influence wrist angle estimates. Electrogoniometers are an alternative to video, but may not be reliable in complex postures. Given the limitations of each method, there is a need to determine the suitability of the measurement methods for field use. Method: Ten participants performed frame-by-frame wrist (flexion–extension, radioulnar deviation) and forearm (pronation–supination) posture estimation for worker tasks from three camera views (top, side, and oblique). Workers were equipped with electrogoniometers to record wrist posture during the tasks. The video estimate data was compared between 2 days and to sensor data. Results: Percent agreement between participants ranged from 53% to 81% across all ratings. Agreement was highest from the side view (66%, κ = 0.56) for flexion–extension and top view for radioulnar deviation (77%, κ = 0.52) and pronation–supination (69%, κ = 0.58). Video–electrogoniometer agreement was lower, with peak agreement from the top view for flexion–extension (57%, κ = 0.49) and radioulnar deviation (68%, κ = 0.30) and the oblique view for pronation–supination (53%, κ = –0.1). Conclusion: Participant estimate agreement was moderate-substantial overall and aligns with previous reports. Disagreement between video and electrogoniometers may be attributed to camera angle and parallax effects and the small magnitude of wrist motions compared to other joints.